Vitamin D receptor signalling regulates the diet-driven metabolic shift during weaning - Neha Jawla; Shubhi Khare; Nidhi Yadav; Ranjan Kumar Nanda; G. Aneeshkumar Arimbasseri (Molecular Metabolism)
Objective: Weaning in mammals is associated with a shift in the metabolism, driven by the differences in the macronutrient composition of milk and post-weaning diet. Milk has a higher fat content compared with the carbohydrate-enriched solid food. Malnutrition during this stage could affect this transition with long-term adverse effects. The role of micronutrients during this transition is not well understood. Methods: We used mice lacking a functional vitamin D receptor (VDR) to study the role of vitamin D signalling in the metabolic transition during weaning. Results: We demonstrate that after weaning, VDR knockout mice exhibit systemic energy deprivation and higher lipolysis in inguinal white adipose tissue, probably due to increased norepinephrine signalling via protein kinase A (PKA) and extracellular signalling-regulated kinase (ERK) pathways. The energy deprivation in vdr−/− mice is associated with defective liver glycogenolysis, characterized by increased expression of protein phosphatase-1 alpha and decreased glycogen phosphorylase activity. However, restoration of serum calcium and phosphate levels by a rescue diet is sufficient to restore energy metabolism in vdr−/− mice. Interestingly, maintaining a high-fat-containing milk-based diet post-weaning could prevent the onset of energy deprivation, liver glycogen storage defect, and adipose atrophy in these mice. Conclusion: Our data show that vitamin D-signalling is essential for the adaptation of mice to the dietary shift from high-fat-containing milk to post-weaning carbohydrate-enriched diets. It also reveals a novel macronutrient–micronutrient interaction that shapes the metabolic flexibility of the individual based on the dietary composition of nutrients.